IMPLEMENTASI AKUNTABILITAS DAN TRANSPARANSI GUNA MENILAI KINERJA PENGELOLAAN ANGGARAN DITINJAU DARI PERMEN PANRB NOMOR 53 TAHUN 2014 DAN NOMOR 88 TAHUN 2021 (STUDI KASUS UPTD LINGKUNGAN PONDOK SOSIAL KEPUTIH SURABAYA) - Dinda Aulia Safitri; Maulidah Narastri (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2026)
The public sector emerged as a response to the collective need for goods and services for the general public. Regulating the allocation and distribution of these goods and services is the government's responsibility to prevent disruptions in the distribution process. Local governments must be responsive in providing public services. This study aims to analyse accountability and transparency in budget management performance in accordance with the Minister of State Apparatus Empowerment and Bureaucratic Reform (PANRB) Number 53 of 2014 and Number 88 of 2021 at the UPTD Liponsos Keputih Surabaya. The method used is qualitative research. This study uses primary data, derived from observations and interviews, as well as secondary data from documentation and several supporting data. Two employees of the UPTD Liponsos Keputih served as informants for this study. The results show that budget management accountability at the UPTD Liponsos Keputih Surabaya has been implemented well and is in accordance with Ministerial Regulations of the Administrative and Bureaucratic Reform (PANRB) Number 53 of 2014 concerning technical instructions for performance agreements, performance reporting, and procedures for reviewing government agency performance reports and Number 88 of 2021 concerning evaluation of government agency performance accountability. In every phase, from planning to reporting, the Regional Technical Implementation Unit (UPTD) demonstrates a strong commitment. Furthermore, budget management transparency at the UPTD Liponsos Keputih Surabaya has been implemented effectively. The budget management supports the principle of information transparency stipulated in the Regulations of the Minister of State Apparatus Empowerment and Bureaucratic Reform No. 53 of 2014 and No. 88 of 2021, as well as the Public Information Disclosure Law.Sektor publik muncul sebagai respons dari kebutuhan kolektif terhadap barang dan layanan untuk masyarakat umum. Pengaturan pengalokasian dan pendistribusian barang dan layanan ini menjadi tanggung jawab pemerintah untuk mencegah proses distribusi yang terhambat. Pemerintah daerah harus tanggap dan responsif dalam memberikan layanan kepada masyarakat. Penelitian ini bertujuan menganalisis akuntabilitas dan transparansi terhadap kinerja pengelolaan anggaran sesuai Permen PANRB Nomor 53 Tahun 2014 dan Nomor 88 Tahun 2021 di UPTD Liponsos Keputih Surabaya. Metode yang digunakan penelitian kualitatif. Penelitian ini menggunakan data primer, yang berasal dari observasi dan wawancara serta data sekunder dokumentasi dokumen serta beberapa data pendukung. Dua karyawan UPTD Liponsos Keputih menjadi informan penelitian ini. Hasil penelitian menunjukkan bahwa akuntabilitas pengelolaan anggaran di UPTD Liponsos Keputih Surabaya telah diterapkan dengan baik dan telah sesuai dengan Permen PANRB Nomor 53 Tahun 2014 Tentang petunjuk teknis perjanjian kinerja, pelaporan kinerja, dan tata cara reviu atas laporan kinerja instansi pemerintahan dan Nomor 88 Tahun 2021 Tentang evaluasi akuntabilitas kinerja instansi pemerintah. Dalam setiap fase, mulai dari perencanaan hingga pelaporan, UPTD menunjukkan komitmen yang kuat. Selain itu, transparansi pengelolaan anggaran di UPTD Liponsos Keputih Surabaya telah dilaksanakan dengan baik. Ini mendukung prinsip keterbukaan informasi yang diatur oleh Permen PANRB Nomor 53 Tahun 2014 dan Nomor 88 Tahun 2021 dan Undang-Undang Keterbukaan Informasi Publik